The role of microRNAs in the idiopathic inflammatory myopathies. Issue 6 (November 2015) - Parkes, Joanna E.; Day, Philip J.; Chinoy, Hector; Lamb, Janine A.
Abstract : Purpose of review: The idiopathic inflammatory myopathies (IIMs) are a group of rare autoimmune disorders characterized by skeletal muscle weakness and inflammation. MicroRNAs (miRNAs) regulate a wide range of developmental and physiological cellular processes. New approaches to investigating the mechanisms involved in IIM, such as investigating the role of miRNAs, are vital for the development of novel therapeutics and/or better diagnostic tools. Recent findings: Identification of dysregulated miRNAs has led to a greater understanding of inflammation, muscle weakness/wasting and extra-muscular organ involvement in IIM. Up-regulation of immune-related miRNAs in muscle, for example, miR-155 and miR-146, is associated with autoimmunity, whereas down-regulation of myogenic miRNAs, including miR-1 and miR-206, is associated with inhibition of muscle regeneration. Disease mechanisms have been explored by altering in-vitro conditions and monitoring miRNA levels of interest, or, alternatively, changing miRNA levels and monitoring possible targets. For example, higher levels of cytokines appear to inhibit myogenic miRNAs in muscle and artificially reducing levels of miR-223 increases protein kinase C-epsilon (PKCε) levels in keratinocytes. Summary: The exciting expansion of the miRNA field adds to our understanding of IIM pathogenesis and may provide future clinical potential either as diagnostic tools or as therapeutics via use of anti-miRNAs or synthetic miRNAs.